Mathematical methods in physics and engineering with Mathematica - Cap, Ferdinand (Chapman & Hall/CRC, 2015)
Demonstrates how to use Mathematica 4.x to solve difficult problems involving ordinary and partial differential equations and boundary value problems. This book helps readers learn by doing with step-by-step recipes useful in both new and classical applications. It includes explanations of various Mathematica commands with examples and exercises.